Aneuploidy promotes intraspecific diversification of the endemic East Asian herb Lycoris aurea complex - Wang, Jinxia; Sun, Lu; Zhu, Hao; Lv, Yanni; Meng, Weiqi; Lv, Guosheng; Zhang, Dong; Liu, Kun (Frontiers in Plant Science, 2022)
Polyploidy has received considerable interest in the past, but aneuploidy and partial rearrangements may also influence genomic divergence. In this study, we reported a comprehensive cytogeographic, morphological and genetic analysis of Lycoris aurea complex throughout its range and attempted to explore the association between aneuploidy and species diversification. The karyotypes of this complex presented aneuploidy variations mainly divided into four cytotypes: Ⅰ (2n = 10m+2T), Ⅱ (2n = 8m+6T), Ⅲ (2n = 7m+8T) and Ⅳ (2n = 6m+10T). Cytotype distributions were highly structured geographically. Two main cytotypes, Ⅱ and Ⅳ, are geographically allopatric. The populations with cytotype Ⅱ are mainly distributed in central China and the southern islands of Japan. Cytotypes Ⅳ is disjunctly distributed in southwestern and southeastern China. The cytotypes with fewer chromosome numbers tend to occur at high latitudes. For analyzing the phylogeographic pattern and genetic structure of this complex, we sequenced four chloroplast DNA fragments (4748 bp in total) of 241 individuals from 42 populations. Extremely high diversity of cpDNA haplotypes was found, with genetic diversity index (Hd) being 0.932 and 98.61% of the genetic variation occurring among populations, indicating that this complex has undergone strong intraspecific differentiation. The cytotype Ⅱ had the highest haplotype diversity (Hd = 0.885), while cytotype Ⅳ harbored the highest nucleotide diversity (π = 4.09×10-3). We detected significant leaf morphological differences not only between cytotype Ⅱ and Ⅳ but also between west lineage and east lineage within cytotype Ⅳ. These results illustrated that aneuploidy contributed to extensive morphological and genetic differentiation in L. aurea complex. It was suggested that L. aurea complex should comprise multiple independent evolutionary lineages, and accurate species delimitation needs to be established further in an integrative taxonomic approach.